The relationship between transport accessibility and employment duration - Jacomien van der Merwe; Stephan Krygsman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The purpose of this research is to investigate whether transport accessibility influences the employment duration of individuals in South Africa. The South African Revenue Service's IRP5 administration datasets, which indicate employment duration and spatial location data (where workers reside and work) for all income earners in South Africa, were used to determine individuals' employment duration, as well as the travel distances between their residence and place of employment. Airline distance was used as a proxy for transport accessibility. The results indicate a negative relationship between increased commuting distance and employment duration for lower-income individuals, with these commuters being more affected by greater travel distances than higher-income groups. Spatial mapping indicates a job-housing mismatch in South African metropolitan areas and limited employment search areas for lower-income workers compared with higher-income workers, leading to further inequality.
Keywords: J64; R12; R40; 330; employment duration; equality; job-housing mismatch; transport accessibility